Prevalence and Characterization of MRSA in a Regional Hospital in Cuenca, Ecuador - Leisen, Erin; Szmanda, Annie (My University, 2015)
Methicillin-resistant Staphylococcus aureus (MRSA) is an antibioticresistant strain of the bacterium Staphylococcus aureus that is responsible for many hospital-acquired infections world-wide. Very little information is currently available on the prevalence of MRSA colonization among patients and staff in Ecuadorian hospitals(1,4). During the summer of 2012, nasal swabs were collected from 494 volunteers in a regional public hospital in Cuenca, Ecuador to determine the prevalence of MRSA colonization within the hospital.
Color poster with text, graphs, charts, and images.
Keywords: Hospital infections; Staphylococcus aureus; MRSA; Posters